Patellofemoral alignment and geometry and early signs of osteoarthritis are associated in patellofemoral pain population. (18th March 2020) - Eijkenboom, Joost F. A.; van der Heijden, Rianne A.; de Kanter, Janneke L. M.; Oei, Edwin H.; Bierma‐Zeinstra, Sita M. A.; van Middelkoop, Marienke
Abstract : Background: Patellofemoral pain (PFP) patients show increased prevalence of patellar malalignment. Structural and alignment abnormalities of the patellofemoral joint (PFJ) may play a role in development of PFP and patellofemoral osteoarthritis (PFOA). Objectives: Evaluating associations of patellofemoral alignment and femoral geometry with bony and cartilaginous abnormalities in PFP patients and healthy control subjects. Methods: Data from a case‐control study were used (64 PFP subjects, 70 control subjects, 57% female, age 23.2 (6.4)). Alignment and femoral geometry measures in the PFJ were determined using MRI. Structural abnormalities in the PFJ associated with OA (bone marrow lesions, osteophytes, minor cartilage defects and Hoffa‐synovitis), quantified cartilage composition (T1ρ relaxation times) in the PFJ and perfusion within the patellar bone were examined using different MRI techniques. Associations were analyzed using regression analyses, adjusted for potential confounders. Results: Lateral patellar tilt was negatively associated with presence of osteophytes on both patella (OR 0.91; 95% CI 0.84 to 0.98), anterior femur (OR 0.92; 95% CI 0.84 to 0.99) and minor cartilage defects on patella (OR 0.91; 95% CI 0.84 to 0.99). Patella alta was positively associated with the presence of bone marrow lesions in the patella and minor cartilage defects (OR 48.33; 95% CI 4.27 to 547.30 and OR 17.51; 95% CI 1.17 to 262.57, respectively). Patella alta and medial patellar translation were positively associated with T1ρ relaxation times within trochlear cartilage (β 5.2; 95% CI 0.77 to 9.58, and 0.36; 95% CI 0.08 to 0.64, respectively). None of the alignment and geometry measures were associated with bone perfusion. Conclusion: Our study implies that associations between patellofemoral alignment and geometry and structural joint abnormalities linked to OA are already present in both PFP patients and healthy control subjects.